Hepatocellular carcinoma after prior sorafenib treatment: Incidence, healthcare utilisation and costs from German statutory health insurance claims data - Johannes Clouth; Astra M. Liepa; Guido Moeser; Heiko Friedel; Magdalena Bernzen; Jörg Trojan; Elena Garal-Pantaler (Health Economics Review, 2018)
Objective: To estimate both the number of patients with hepatocellular carcinoma (HCC) eligible annually for second-line therapy following sorafenib in Germany and the healthcare costs accrued by patients meeting eligibility criteria. Methods: Patients with an HCC diagnosis and one or more sorafenib prescription were identified from samples of > 3 million insured persons in each of 2012, 2013 and 2014 using the anonymised Betriebskrankenkasse health insurance scheme database. Incidence rates from 2013 were extrapolated to the German population using data from the statutory health insurance system database and Robert Koch Institute. Resource use and cost data were collected for a subset of patients with follow-up data post-sorafenib. Results: Between 1032 and 1484 patients with HCC in Germany (893-1390 publicly insured patients) were estimated as likely to be eligible for second-line therapy after sorafenib annually. For post-sorafenib analyses, 117 patients were identified with HCC, one or more sorafenib prescription and considered potentially eligible for second-line treatment, 15 of whom were alive after 12 months' follow-up. Total mean costs per patient accrued in the 12 months after sorafenib treatment ended were exteuro11,152 (hospital care, exteuro6483 [58.1%]; outpatient prescriptions, exteuro3137 [28.1%]). Conclusion: The estimated number of publicly insured HCC patients annually eligible for second-line therapy in Germany was < 1400 and mean total costs accrued in the year after completion of sorafenib therapy were approximately exteuro11,000 per patient for the German statutory healthcare system. These estimates can be used when evaluating the budgetary impact of new second-line therapies for advanced HCC in Germany.
Keywords: 330; Hepatocellular carcinoma; Germany; Second line; Sorafenib; Health economics; German statutory health insurance claims data